THE EFFECT OF BRAND AMBASSADORS AND BRAND IMAGE ON PURCHASING DECISIONS - Ansir Launtu (International Journal of Multidisciplinary Research and Literature, 2023)
This study aims to determine, test and analyze the influence of brand ambassadors and brand image on purchasing decisions (a survey of Instagram users specifically for the Makassar area). Data analysis used multiple regression equations and the classic assumption test, one of the methods used to determine the number of samples was using the Slovin formula, the sample used was 30 Instagram users in the Makassar Region. The research data were obtained from questionnaires, literature studies, and direct interviews with related parties according to the research objectives. The results of this study indicate that the brand ambassador and brand image variables simultaneously and partially have a significant effect on purchasing decisions (a survey of Instagram users specifically for the Makassar area). The coefficient of determination is 0.592 which indicates that the ability of the independent variables to predict the dependent variable is 59%. 41% is influenced by other factors not examined by the author